IMPLEMENTASI FP-GROWTH DAN FUZZY TSUKAMOTO UNTUK MENENTUKAN PERSENTASE KUOTA JALUR MASUK PERGURUAN TINGGI - Khairunnisa, Nafa; Jumadi, Jumadi; Taufik, Ichsan (SKANIKA: Sistem Komputer dan Teknik Informatika, 2025)
Every university strives to achieve or maintain excellent accreditation. Students who graduate with a satisfactory predicate play an important role in determining the accreditation. According to BAN-PT 2021, a university is considered excellent if it has students with a maximum study period of 4.5 years and an average GPA ≥ 3.25. One way to maintain it is to optimally manage the distribution of quotas for the New Student Admission (PMB) entrance pathway. This study aims to investigate how the variables of GPA, study period, and entry path in the data of graduates relate to each other. To get the association pattern between these variables, FP-Growth is used. Furthermore, the percentage of quota distribution is calculated using Fuzzy Tsukamoto. From this research, the accuracy of the model is 94.42% and the precision value is 62.5%, which indicates that the method used is effective in helping determine the optimal quota distribution for PMB. Thus, these results can be used to support university policies in determining a more appropriate quota distribution to support the achievement of superior accreditation.